Plant Taxonomic Diversity: An Assessment on Gandhamardan Hill Range of Western Odisha, India - Bhadra, A. K.; Pattanayak, S. K.; Dhal, N. K. (Indian Forester, 2020)
Present study records 232 plant species which is 8.5% of total 2727 species found in Odisha. All species are distributed over six prevalent forest types such as Tropical semi-evergreen forest, Tropical drydeciduous forest, Scrub-woodland, Bamboo forest, Scrub forest and Grass land of Gandhamardan hill ranges. Tree, shrub, LTC (Lianas, Twinner and Climber) and herb represent 37.50%, 15.09%, 12.07% and 35.34% of the total species. 232 plant species comes under 189 genera and 66 families. Tree community having GBH > 15cm (Tree-1) consists of 86 species, 71 genera and 35 families. Tree community having GBH < 15cm (Tree-2) has 58 species, 51 genera and 30 families. Shrub community represents 34 species, 33 genera and 23 families. LTC represents 26 species, 21 genera and 12 families. Herb community represents 82 species, 69 genera and 25 families. Similarly, seedling community is having 101 species, 90 genera and 44 families. The ten most dominant families in the region are Poaceae, Fabaceae, Rubiaceae, Euphorbiaceae, Acanthaceae, Lamiaceae, Cyperaceae, Moraceae, Rhamnaceae and Apocynaceae. 161 out of total 189 genera are represented by single species. In other words, 69% of total species occurrence is spread over 85% of total genera which indicates the higher taxonomic diversity of the forest area.